1994
DOI: 10.1128/aac.38.4.773
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and nucleotide sequence of Mycobacterium tuberculosis gyrA and gyrB genes and detection of quinolone resistance mutations

Abstract: The emergence of multidrug-resistant strains ofMycobacterium tuberculosis has resulted in increased interest in the fluoroquinolones (FQs) as antituberculosis agents. To investigate the frequency and mechanisms of FQ resistance in M. tuberculosis, we cloned and sequenced the wild-type gyrA and gyrB genes, which encode the A and B subunits of the DNA gyrase, respectively; DNA gyrase is the main target of the FQs. On the basis of the sequence information, we performed DNA amplification for sequencing and single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
296
2
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(318 citation statements)
references
References 34 publications
18
296
2
2
Order By: Relevance
“…Some researchers have described mutations that caused amino acid substitutions but not drug resistance (30,33,39). In the present study, we identified several novel mutations that cause amino acid substitutions but do not confer drug resistance.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Some researchers have described mutations that caused amino acid substitutions but not drug resistance (30,33,39). In the present study, we identified several novel mutations that cause amino acid substitutions but do not confer drug resistance.…”
Section: Discussionmentioning
confidence: 57%
“…Mutations in the FQ resistancedetermining region (QRDR) in gyrA are responsible for resistance in at least 96% of FQ-resistant M. tuberculosis isolates (17,30,39). In the present study, we found one novel mutation, E21Q, in gyrA, and all isolates tested, except the H37Rv strain, contained this mutation.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Resistance to fluoroquinolones and second-line aminoglycosides is most frequently associated with mutations in gyrA and gyrB and in rrs, respectively. Studies have demonstrated that by targeting mutations in codons 90, 91, and 94 in gyrA, approximately 70 to 90% of all fluoroquinolone resistance can be accurately predicted (2,5,17). Similarly, mutations in the rrs gene, particularly the hotspot region from nucleotides 1401 to 1484, can accurately predict resistance to second-line aminoglycosides (10,16).…”
mentioning
confidence: 99%